Invasive Klebsiella pneumoniae liver abscess syndrome complicated by carbapenem-resistant Acinetobacter baumannii infection: a case report - Feng, Qiupeng; Yuan, Hua; Ma, Jin; Guo, Zhiqiang; Xia, Xiaohua; Zhao, Guang (Frontiers in Medicine, 2025)
BackgroundA liver abscess caused by hypervirulent Klebsiella pneumoniae can lead to multiple invasive extrahepatic infections, including lung abscesses, endophthalmitis, brain abscesses, and necrotizing fasciitis. This condition, known as Klebsiella pneumoniae liver abscess invasion syndrome, progresses rapidly and is associated with severe illness, high disability rates, and significant mortality. However, bloodstream infections with co-infection involving carbapenem-resistant Acinetobacter baumannii are exceedingly rare.Case presentationThe Emergency Medicine Department of the First People’s Hospital of Kunshan successfully treated a male patient diagnosed with liver, lung, and prostate abscesses. The patient underwent puncture and drainage, with analysis of the drainage fluid, sputum culture, and metagenomic next-generation sequencing (m-NGS) revealing a co-infection with blood-borne Klebsiella pneumoniae and Acinetobacter baumannii. Guided by drug sensitivity test results, the patient received treatment with polymyxin and cefoperazone sodium-sulbactam sodium for infection control and liver protection. The treatment was successful, and the patient fully recovered and was discharged.ConclusionBy reporting this rare case and highlighting the drug resistance of the bacteria, we propose a new diagnosis and treatment plan for managing Klebsiella pneumoniae combined with carbapenem-resistant Acinetobacter baumannii infection, along with a literature review.